Association between the American Heart Association’s New Life’s Essential 8 Metrics and Depression Symptom in U.S General Adults, Finding from NHANES 2005-2018 - Ruan, Zhuoer; Zhu, Jie; Xu, Shengnan (Frontiers in Psychiatry, 2024)
BackgroundThe American Heart Association (AHA) recently introduced a new metric for promoting cardiovascular health (CVH) called Life’s Essential 8 (LE8). However, there has been no investigation into the relationship between levels of LE8 and the risk of depression symptom. Therefore, our objective was to determine this association using a nationally representative sample of U.S adults.MethodsUtilizing cross-sectional data from the NHANES spanning the years 2005 to 2018, we computed scores for both overall CVH and individual LE8 components. The survey-weighted logistic regression models were conducted to determine whether LE8 was associated with depression symptom.ResultsA total of 25,357 adults aged 20 and above were included in the study, representing a population of 1,184 million non-institutionalized U.S residents. The study revealed that individuals with positive scores in both individual and total LE8 metrics were less likely to experience depressive symptoms compared to those with negative scores. Furthermore, a significant negative linear trend was observed, showing that as the overall number of favorable LE8 scores increased, the likelihood of depressive symptoms decreased.ConclusionAttaining a higher CVH score, as defined by the LE8, is strongly linked to a lower risk of experiencing depressive symptoms in adult residents of the U.S.